2019
DOI: 10.1038/s41598-019-55349-7
|View full text |Cite
|
Sign up to set email alerts
|

A New Method to Reconstruct in 3D the Emission Position of the Prompt Gamma Rays following Proton Beam Irradiation

Abstract: A new technique for range verification in proton beam therapy has been developed. It is based on the detection of the prompt γ rays that are emitted naturally during the delivery of the treatment. A spectrometer comprising 16 LaBr3(Ce) detectors in a symmetrical configuration is employed to record the prompt γ rays emitted along the proton path. An algorithm has been developed that takes as inputs the LaBr3(Ce) detector signals and reconstructs the maximum γ-ray intensity peak position, in full 3 dimensions. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…Panaino et al make use of coincidence between two consecutive gamma-rays from the deexcitation of 16 O (2.75 MeV followed by 6.13 MeV with 25 ps decay time) to reconstruct in 3D the emission vertex position, by means of a nearly-4π multi-detector of high temporal resolution [59]. This is made possible since the two gamma emissions occur at the same location.…”
Section: D Imaging With Dual Pg Coincidencementioning
confidence: 99%
“…Panaino et al make use of coincidence between two consecutive gamma-rays from the deexcitation of 16 O (2.75 MeV followed by 6.13 MeV with 25 ps decay time) to reconstruct in 3D the emission vertex position, by means of a nearly-4π multi-detector of high temporal resolution [59]. This is made possible since the two gamma emissions occur at the same location.…”
Section: D Imaging With Dual Pg Coincidencementioning
confidence: 99%
“…The emission characteristics of the prompt gamma was investigated and prompt gamma detection with an ideal condition, according to the paper, was simulated. Panaino et al recently reported 3D reconstruction algorithm for the prompt gamma images with Geant4-based simulation of the detection systeam and 180 MeV proton beams that were delivered to water phantom (Panaino et al 2019). They located the proton range in 3D coordinates within the difference of a few milimeters compared to the simulated dose distribution.…”
Section: Nuclear Imagingmentioning
confidence: 99%